IdealCity: A hybrid approach to seismic evacuation modeling. (March 2021) - Battegazzorre, Edoardo; Bottino, Andrea; Domaneschi, Marco; Cimellaro, Gian Paolo
Highlights: The possibility to simulate the community response to disasters has several relevant applications. This work presents IdealCity, a hybrid model for evacuation simulation. IdealCity includes the built environment, transport networks, city residents and emergency service. The model has been used to simulate different seismic events in a real city. Simulation results support community response analyses and resource planning. Abstract: In recent years, the analysis of the community response in case of disastrous events has become a research topic of paramount relevance due to the increasing number of calamities like flooding, hurricanes, and earthquakes. In particular, the possibility to use computer simulations to model and study the behavior of thousands of people during an emergency evacuation can provide valuable information to support many processes involved in emergency management. To this end, this work presents IdealCity, a hybrid model for evacuation simulation that couples the representation of the built environment and the transportation network with an agent-based simulation of the urban population. IdealCity can estimate the buildings' damages and debris generated by a seismic event along with their effects on the other model layers (the agents and the roads). Besides that, the simulation takes into consideration as well the emergency response system by modeling shelters, hospitals, and ambulances (each of which has a specific behavior within the environment). The model has been implemented and tested in a challenging test-bed that considers about 900, 000 individuals, four different seismic scenarios, and three different times of the day. Results show that IdealCity can be used not only for predicting the population response but also for allowing decision-makers to estimate and intervene on critical response parameters, thus improving the inherent community resilience.